Safety work versus the safety of work. (January 2019) - Rae, Andrew; Provan, David
Highlights: Safety work, a set of activities, is distinct from operational safety, an outcome. Safety work is a specialist type of institutional work. Safety work is often performed for purposes other than operational safety. To understand safety work it is important to understand the non-operational purposes. Abstract: 'Safety work' consists of activities, conducted within organisations, that have the primary purpose of managing safety. Safety work is distinct from operational work, which directly achieves the primary objectives of the organisation. Safety work is also distinct from the 'safety of work', which is the prevention of injury. In this paper, we argue that safety work is primarily a performance rather than goal-directed behavior. It may contribute to the safety of work, but this is only part of its purpose. Our argument is presented in the form of a model for organisational safety activity that represents safety as a special case of 'institutional work'. Evidence of the 'safety work' takes the place of evidence of the 'safety of work', which is extremely difficult to measure or demonstrate in its own right. Even where it does not contribute to the safety of work, safety work may be necessary for organisations to make sense of safety in an uncertain world. If organisations did not perform safety work, they would be unable to convince stakeholders that they were doing enough for safety, which would in turn prevent them from pursuing their core business.